2018
DOI: 10.3389/fphys.2018.00332
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Reactive Oxygen Species and Nitric Oxide on Red Blood Cell Deformability

Abstract: The main function of red blood cells (RBCs) is the transport of respiratory gases along the vascular tree. To fulfill their task, RBCs are able to elastically deform in response to mechanical forces and, pass through the narrow vessels of the microcirculation. Decreased RBC deformability was observed in pathological conditions linked to increased oxidative stress or decreased nitric oxide (NO) bioavailability, like hypertension. Treatments with oxidants and with NO were shown to affect RBC deformability ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 46 publications
1
57
0
3
Order By: Relevance
“…Erythrolysis was a condition found only in EKO mice and possibly consequent to the severe hypercholesterolaemia that has been shown to increase the osmotic fragility of RBC (Fessler, Rose, Zhang, Jaramillo, & Zeldin, 2013). In addition, fenretinide treatment is associated to an augmented ROS production (Cuperus, Leen, Tytgat, Caron, & van Kuilenburg, 2010), which in turn reduces RBC deformability (Diederich et al, 2018). These two effects are synergized in EKO-Fen only, leading to peripheral haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrolysis was a condition found only in EKO mice and possibly consequent to the severe hypercholesterolaemia that has been shown to increase the osmotic fragility of RBC (Fessler, Rose, Zhang, Jaramillo, & Zeldin, 2013). In addition, fenretinide treatment is associated to an augmented ROS production (Cuperus, Leen, Tytgat, Caron, & van Kuilenburg, 2010), which in turn reduces RBC deformability (Diederich et al, 2018). These two effects are synergized in EKO-Fen only, leading to peripheral haemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a study by Diederich reported that NO donors would be able to preserve RBC deformability in situations where oxidative stress would be enhanced [49]. Oxidative stress plays a critical role in the pathophysiology of SCA [50].…”
Section: Discussionmentioning
confidence: 99%
“…This review will briefly summarize what is currently known about the involvement of RBCs in hemostasis and thrombosis and its underappreciated importance. RBCs increase blood viscosity because of a rise in hematocrit, an increase in RBC aggregation or a decrease in RBC deformability (increasing flow resistance) Pro [2][3][4][5] Conversely, anemia is associated with low blood viscosity and bleeding tendency as a result of reduced platelet margination toward endothelium and enhanced NO availability Anti [2][3][4][5] RBCs undergo shear-dependent reversible aggregation mediated by plasma proteins (mainly fibrinogen and immunoglobulins) and/or local osmotic gradient Pro [14][15][16][70][71][72][73][74] RBCs with increased rigidity occlude small vessels Pro [11,12] Deformability of RBCs reduces frictional resistance to flow Anti [8,[11][12][13]] RBCs maintain biconcave shape and a high surface-to-volume ratio as a result of cytoskeleton and water/ions balance Pro or anti [5] RBCs migrate to the center of blood flow and push platelets toward the endothelium (margination) in a hematocrit-and shear-dependent manner Pro [59][60][61] Effects on platelet reactivity RBCs increase platelet adhesion and aggregation by release of ADP and thromboxane A 2 Pro [66,67] RBCs form aggregates with platelets via adhesive molecules (ICAM-4 and fibrinogen with aIIbb3)…”
Section: Introductionmentioning
confidence: 99%